Application of AI technology in interior design - Chen Zixuan; Wang Xiang (E3S Web of Conferences, 2020)
AI technology is coming into our life in recent years. Science and technology also changing and improving our interior design. The overall national strength has grown remarkably, and the level of science and technology has reached the world-class level. This paper starts from the combination of AI and home design, multi-angle analysis of the current development and future prospects. According to the bedroom, kitchen, children’s items storage problems to provide solutions. Storage is an important problem for designers, and also a difficult problem for users in their life. However, with the help of AI, it can bring first-class experience for users. This paper will carry out analysis and research from this point.